Redefining Hadith by The Zahirism of Ibn Hazm - H Zuhri (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The perception of Ibn Hazm's thought on hadith as a Muslim intellectual who always puts forward the principles of textual Zahirism (dhāhiriyyat al-nash) in establishing a legal conclusion (istidlāl al-hukm) has implications for the general principles of understanding and position of hadith or al-sunnah. These implications will generally lead to the strengthening of the dhāhiriyyat al-nash paradigm or vice versa. This study employs a qualitative method with historical analysis and literature study along with relevant information of the study.This study explores Ihn Hazm's ideas about hadith, written in several of his works. Thus, it can be concluded that Ibn Hazm did not just use hadith for the sake of his madhab; he was also suspected of redefining or reconceptualizing various understandings of hadith. Finally, Ibn Hazm has rationalized the hadith according to the context and paradigm he is carrying. Hadith terminology cannot separate from the influence of discourse outside of hadith, such as knowledge, law, politics, and social religion.